2020
DOI: 10.1097/iae.0000000000002793
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Vascular Density in the Choroid After Treatment With Photodynamic Therapy Combined With Aflibercept in Patients With Polypoidal Choroidal Vasculopathy

Abstract: Purpose: To investigate changes of vascular density in the choroid of patients with polypoidal choroidal vasculopathy treated with photodynamic therapy (PDT) combined with intravitreal aflibercept. Methods: This study examined 12 eyes of 12 patients, who were diagnosed as polypoidal choroidal vasculopathy. All patents underwent optical coherence tomography before and at 3 months after PDT combined with intravitreal aflibercept treatment. Using en face o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Vascular occlusion at the level of the choroidal capillary plate after PDT has been reported previously [9,10]; however, occlusion of large vessels, as observed in this study, has not been reported before.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Vascular occlusion at the level of the choroidal capillary plate after PDT has been reported previously [9,10]; however, occlusion of large vessels, as observed in this study, has not been reported before.…”
Section: Discussionsupporting
confidence: 48%
“…On the other hand, PDT also affected normal choroidal vessels, specifically both normal choriocapillaris and middle and large choroidal vessels [10,14,15]. As mentioned in the introduction, the circumscribed hypofluorescent area where the PDT had been exposed was detected in IA after PDT treatment, and the area contained both normal and abnormal choroidal vessels [9].…”
Section: Discussionmentioning
confidence: 93%
“…The mechanism of PDT in CSC is presumably based on the formation of free radicals upon illuminated treatment area, which leads to vascular endothelium damaging, choriocapillaris narrowing, hypoperfusion and subsequent choroidal vascular remodeling [4,[10][11][12]. The mean diameter of the dilated choroidal vessel decreases after the PDT [4], and PDT reduces the vascular density in the choriocapillaris and middle layer of the choroid [31]. This study revealed that the choroidal volume and thickness decreased even in non-irradiated area of PDT eyes.…”
Section: Discussionmentioning
confidence: 99%